Increased systemic vascular resistance in Atlantic salmon, Salmo salar L., affected with amoebic gill disease - Melanie Leef; Hill, JV; Harris, JO; Powell, MD (2007)
Previous investigations into the pathophysiology of amoebic gill disease (AGD) have suggested that there are probable cardiovascular effects associated with this disease. In the present study Atlantic salmon, Salmo salar L., were experimentally infected by cohabitation with diseased individuals. Two commonly used vasodilators, sodium nitroprusside (SNP) and captopril, the angiotensin-converting enzyme (ACE) inhibitor, were used as tools to investigate possible vasoconstriction and/or renin-angiotensin system (RAS) dysfunction in AGD-affected animals. Within the SNP trial, results showed that AGD-affected fish exhibited lowered cardiac output (Q), lowered cardiac stroke volume (V S) and a significantly elevated systemic vascular resistance (R S) compared with non-affected naïve counterparts. These effects were totally abolished following SNP administration (40 μg kg -1), however significant cardiovascular effects associated with SNP were not observed. Within the captopril trial, where AGD-affected fish were more diseased compared with the SNP trial, a significant hypertension was observed in AGD-affected fish. Captopril administration (10 -4 mol L -1 at 1 mL kg -1) resulted in a significant drop in dorsal aortic pressure (P DA) for both AGD-affected and naïve control fish. In terms of peak individual responses, captopril administration effectively lowered P DA in both AGD-affected and naïve control groups equally. The drop in P DA following SNP administration however was significantly greater in AGD-affected fish potentially suggesting disease-related vasoconstriction. The lack of significant cardiovascular effects directly associated with both SNP and captopril administrations possibly relate to the 6 h recovery period following surgical procedures. However, while variable, these results do suggest that there are significant cardiovascular effects including vasoconstriction and hypertension associated with AGD. © 2007 The Authors.